Endemic Transmission of Visceral Leishmaniasis in Bhutan (2012)
ABSTRACT: Visceral leishmaniasis was first reported in Bhutan in 2006. We conducted studies of the parasite, possible vectors and reservoirs, and leishmanin skin test and risk factor surveys in three villages. Nineteen cases were reported from seven districts. Parasite typing yielded two novel microsatellite sequences, both related to Indian L. donovani. In one case village, 40 (18.5%) of 216 participants had positive leishmanin skin test results, compared with 3 (4.2%) of 72 in the other case village and 0 of 108 in the control village. Positive results were strongly associated with the village and increasing age. None of the tested dogs were infected. Eighteen sand flies were collected, 13 Phlebotomus species and 5 Sergentomyia species; polymerase chain reaction for leishmanial DNA was negative. This assessment suggests that endemic visceral leishmaniasis transmission has occurred in diverse locations in Bhutan. Surveillance, case investigations, and further parasite, vector, and reservoir studies are needed. The potential protective impact of bed nets should be evaluated.